2021
DOI: 10.3390/nu13010146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breastfeeding on Maternal Body Composition in Moroccan Lactating Women during Twelve Months after Birth Using Stable Isotopic Dilution Technique

Abstract: Background: Exclusive breastfeeding during the first six months of an infant’s life is an important factor for their optimal growth and health. Breastfeeding also has maternal benefits and can assist with postpartum weight loss. As shown by previous studies, postpartum weight retention can contribute to obesity. Objective: To quantify the human milk and evaluate the effect of breastfeeding on maternal weight loss during the 12 months postpartum. Method: This study included 70-mother–baby pairs. Infants’ intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Differently, mothers evaluated by Gridneva et al (45) , if compared to mothers included in the present study, show higher weight and adiposity even if they were evaluated at 2 months after the delivery. In a recent study conducted by Rabi et al (46) on mothers exclusively breast-feeding their 1-month babies, FM% is similar to that found in the present study, while FMI is higher. The FMI of IMI-2 group is under the cut-off value considered for the screening of the presence of metabolic syndrome in adult women (47) , while that of IMI-1 is slightly higher.…”
Section: Discussionsupporting
confidence: 91%
“…Differently, mothers evaluated by Gridneva et al (45) , if compared to mothers included in the present study, show higher weight and adiposity even if they were evaluated at 2 months after the delivery. In a recent study conducted by Rabi et al (46) on mothers exclusively breast-feeding their 1-month babies, FM% is similar to that found in the present study, while FMI is higher. The FMI of IMI-2 group is under the cut-off value considered for the screening of the presence of metabolic syndrome in adult women (47) , while that of IMI-1 is slightly higher.…”
Section: Discussionsupporting
confidence: 91%
“…Free glutamine and glutamate in human milk significantly increase by ≤350% and 40%, respectively, within the first 6 months of lactation [ 12 , 26 ]. However, lactation is accompanied by a mild catabolic state in pigs, horses, mice, and humans, characterized by a loss of fat-free mass and decreased glutamine concentrations in plasma and skeletal muscle (indicative of endogenous proteolysis) [ [27] , [28] , [29] , [30] , [31] ]. Therefore, understanding maternal glutamine metabolism during lactation is important both to maternal and neonatal health.…”
Section: Discussionmentioning
confidence: 99%
“… 8–13 While an intervention to promote breastfeeding duration did not result in lower percentage of body fat in a large cluster-randomized trial, 14 one cohort study showed a beneficial association between breastfeeding and fat mass index (FMI) in women having had a child in the last 5 years 9 and two prospective studies suggested that exclusive breast feeding was associated with lower fat mass than mixed breastfeeding. 15 16 In addition, breastfeeding has been associated with a lower visceral adipose tissue in some studies. 17–19 Although existing studies that investigated the relationship between breastfeeding duration and lean mass are limited, no significant relationships have been reported.…”
Section: Introductionmentioning
confidence: 99%